Composition, Types, and Abundance of Microplastics in Water, Sediments, and Blood Clams (Anadara granosa) in the Coastal Waters of Sinaboi, Rokan Hilir Regency - Rinaldy, Rahmat; Amin, Bintal; Nedi, Syahril (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2026)
Microplastics are plastic particles smaller than 5 mm that are difficult to degrade and tend to persist for long periods. This study aims to analyze the types and abundance of microplastics, as well as differences in abundance and their relationships in water, sediment, and blood clams (Anadara granosa). This study was conducted in the waters off Sinaboi Beach, Rokan Hilir Regency, and continued at the Marine Chemistry Laboratory, Department of Marine Science, Faculty of Fisheries and Marine Sciences, Universitas Riau. The method used was a survey employing a purposive sampling approach. The results of this study indicate that the composition of microplastic types found in the waters of Sinaboi Beach included fibers, fragments, films, foams, and granules (pellets); however, in the sediments and blood clams, only granules (pellets) were found. The average abundance of microplastics in water, sediment, and blood clams was 1,467 particles/L, 1,299 particles/g, and 6,844 particles/g, respectively. Statistical analysis showed that the abundance of microplastics in water, sediment, and blood clams based on sampling stations did not differ significantly (p > 0.05). Microplastic abundance in blood clams differed significantly from that in water and sediment (p < 0.05), whereas the comparison between water and sediment showed nearly equivalent abundance levels (p > 0.05). The strongest relationship was found between microplastic abundance in blood clams and sediment, showing a moderate positive correlation